Factors associated with mortality among patients with penetrating non-compressible torso hemorrhage in South Africa: A retrospective cohort study - Smitha Bhaumik; Adane F. Wogu; Lani Finck; Maria Jamison; Mengli Xiao; Julia Finn; Hendrick Lategan; Janette Verster; Shaheem de Vries; Craig Wylie; Lesley Hodson; Mohammet Mayet; et al. (African Journal of Emergency Medicine)
Introduction: Non-compressible torso haemorrhage (NCTH), resulting from penetrating trauma to the chest, abdomen, or pelvis, places patients at high risk of death. The objectives of this study are to characterize the injury profile of patients with penetrating NCTH who receive care within a tiered public trauma system in South Africa and to identify factors associated with mortality. Methods: This is a secondary analysis of clinical data collected from Sept-2021 through Dec-2023 across 6 hospitals, 4 ambulance bases, and 2 mortuaries in the Western Cape Province that form a cohesive trauma referral pathway. The study included patients age ≥18 years with penetrating NCTH who arrived at the hospital within 3 h and received blood products within 6 h of injury. NCTH was defined as Abbreviated Injury Scale (AIS) ≥ 2 to chest, abdomen or pelvis, with a systolic blood pressure ≤ 100 mm Hg. Data were analysed using multivariable logistic regression and Cox proportional hazards modelling. Results: There were 202 patients with penetrating NCTH; median age was 29 years, 94 % male, injured by stab wounds (66 %) and gunshot wounds (31 %). Most patients (85 %) sustained injuries to the chest, 33 % to the abdomen, and 1.5 % to the bony pelvis. In a multivariable logistic regression model, elevated Triage Early Warning Score (TEWS ≥7) (OR 4.45, 95 % CI 1.58–13.90), elevated New Injury Severity Score (NISS >25) (OR 4.35, 95 % CI 1.45–16.30), anatomic injury to the abdomen/pelvis (OR 2.76, 95 % CI 1.03–7.74), and receipt of acute airway intervention (OR 4.97, 95 % CI 1.94–13.20) were significantly associated with 7-day in-hospital mortality. Conclusion: Among patients with penetrating injuries to the torso, high triage scores, high injury severity, early airway interventions, and penetrating abdominal trauma were associated with elevated mortality risk.